2022
DOI: 10.1186/s12940-021-00821-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple neonicotinoids in children’s cerebro-spinal fluid, plasma, and urine

Abstract: Background Neonicotinoids (NN) are selective neurotoxic pesticides that bind to insect but also mammal nicotinic acetycholine receptors (nAChRs). As the most widely used class of insecticides worldwide, they are ubiquitously found in the environment, wildlife, and foods, and thus of special concern for their impacts on the environment and human health. nAChRs are vital to proper brain organization during the prenatal period and play important roles in various motor, emotional, and cognitive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
(44 reference statements)
1
27
0
1
Order By: Relevance
“…Studies done using in vitro models have reported that some metabolites are more potent than the corresponding parent NEO because of their higher affinity to nicotinic nicotinic acetylcholine receptors. 8 A recent study reported that N-dm-ACE concentrations in 93% of CSF samples (13/14) collected from children treated for leukemia and lymphomas were within an order of magnitude ( ) 9 of the concentrations detected in our study. The potential neurotoxic effects of N-dm-ACE to the human CNS should be considered comprehensively.…”
Section: Resultssupporting
confidence: 68%
“…Studies done using in vitro models have reported that some metabolites are more potent than the corresponding parent NEO because of their higher affinity to nicotinic nicotinic acetylcholine receptors. 8 A recent study reported that N-dm-ACE concentrations in 93% of CSF samples (13/14) collected from children treated for leukemia and lymphomas were within an order of magnitude ( ) 9 of the concentrations detected in our study. The potential neurotoxic effects of N-dm-ACE to the human CNS should be considered comprehensively.…”
Section: Resultssupporting
confidence: 68%
“…In the U.S., it is estimated that more than 3.5 million kg of NNs are applied to crops annually. Perceived as a safer alternative to organophosphate and carbamate-based pesticides while also offering broad spectrum toxicity, easy application, and high environmental persistence (fewer required treatments), NNs increasingly became the most commonly used commercial insecticide since the pyrethrum-based pesticides (1980s). ,,,, Research suggests that NN usage has negative implications for both pollinating insects and human health, as the compounds are found in increasing concentrations in drinking water as well as children’s spinal fluid, blood, and urine . Additionally, it is now believed that targeted pests are developing resistance to certain NN pesticides, which causes an increase in the number and concentration of applications.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 8 , 10 , 13 Research suggests that NN usage has negative implications for both pollinating insects and human health, as the compounds are found in increasing concentrations in drinking water as well as children’s spinal fluid, blood, and urine. 14 Additionally, it is now believed that targeted pests are developing resistance to certain NN pesticides, which causes an increase in the number and concentration of applications. This increase, in turn, exacerbates the risk to both pollinators and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Compelling evidence points to a meaningful association between exposure to NNIs and mental diseases in rural populations [ 14 , 15 ]. Given their penetrability across the placenta [ 16 ] and blood-brain barrier [ 17 ], NNIs are likely to alter neurodevelopment in humans [ 18 , 19 ]. NNI-induced toxicity has already been probed in rodent neurons.…”
Section: Introductionmentioning
confidence: 99%